Tipe Echolokasi serta Struktur Larynx pada Miniopterus dan Rhinolophus - Abdul Rachman; Johanes Sugiyanto; Luthfi Nurhidayat; Ardaning Nuriliani; Aswi A. Rofiqoh; Agus Hermawan; Roesma Narulita (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
A bat is the only mamal with true flight ability and have capability to perform echolocation. Miniopterus and Rhinolopus are bat species that have some different morphological characteristics but both of them commonly live in the cave. The research were purposed to study the differences and connection of echolocation call type and larynx’s structure of Miniopterus and Rhinolopus The two bat species were collected from 20th and 23th cave of Japanese Cave Complex, Kaliurang, Sleman, Yogyakarta. Specimens were taken to the laboratory for further analysis. Echolocation signals of both bat species were recorded using ultrasonic microphone and were analyzed with Batscan 9.0 software. Specimens were subjected for anatomical and histological structure analysis of the larynx. Anatomical structure observations were carried out with specimens dissection and they were fixed in 20% formol solution. Some samples of larynx of each species were processed and stained with Alizarin Red’s-Alcian Blue staining for larynx’s bones observation. Histological preparation of larynx was performed using paraffin method and stained with Hematoxylin-Eosin and MAF. The results showed that echolocation signals of Minipterus have lower frequency (peak frequency between 44.1-51.6kHz) compared to that of Rhinolopus (peak frequency between 54.4-64.1 kHz). However, Miniopterus has better ability to modulate the signal frequency than Rhinolopus Both species are able to produce a long-duration signal but Rhinolopus can produce longer signal duration. These results can be related to the differences of larynx’s anatomical and histological structure of both species which are equally able to keep the intensity of echolocation signals but have different work mechanisms.